Drivers to equity valuation: perpetuities or annuities approach? An application to the main european stock markets - Reis, Pedro (2019)
Academics and practitioners have been applying equity valuation methods mainly based on discount cash flow models, residual income models, or dividend discount models combined with balance sheet and income statement multiples of market comparables to analyse share price, provide price targets for investors, or even as a basis for transactions such as mergers and acquisitions (M&A). Most of these methods rely on mathematical deductions of growing or constant perpetuities or near perpetuities (such as annuities) to attain market values. However, it is of the utmost relevance for valuation to verify how the theoretical models relate with real values, and what their relationship is with companies’ past age. Beyond stating a non-linear relationship for valuation models and ascertain important valuation drivers, using a sample of more than 3,400 European companies with cross section data, this paper contributes to the improvement of valuation model’s effectiveness by inducing non-explicit period valuation modifications to long-term annuities and perpetuities, considering class age intervals. This paper’s originality is supported by the study of the relationship of past company age with predicted annuities, the proof of non-compliance of perpetuity-based valuation models, and the contribution of new value drivers for valuation purposes.